Probiotic Usage as Therapy on Diabetes Mellitus Type II. A Literature Review - Murti, Lendy Nugroho Wisnu (Brawijaya University, 2019)
A B S T R A C TBackground: Type 2 diabetes has turned into a worldwide medical issue. Probiotic as the microorganisms in the intestinal tract has the potential impact to anticipate the improvement of insulin opposition and glycemic control in patients with type 2 diabetes. This literature review focused on the effects, mechanism of action and potential utilization of probiotic in type 2 diabetes. Results: As therapy in type 2 diabetes, probiotic ready to bring down fasting glucose, HbA1C and HOMA-IR percentage or increment insulin levels. Dicussion: The impact of the probiotic agent acquired on type 2 diabetes through the decrease of lipopolisacharide (LPS), increased Â short chain fatty acids (SCFA), inhibition of immune response and oxidative stress, increased Â glucagon like peptide-1 (GLP-1), secretion of insulinotropic polypeptides, or increased activity of Â glucose transporter-4 (GLUT 4). Conclusion: Probiotic can be a choice to keep up insulin sensitivity and anticipate the beginning of hyperglycemia in type 2 diabetes.